Effectiveness and acceptability of lidocaine spray in reducing perineal pain during spontaneous vaginal delivery: randomised controlled trial. Issue 7559 (28th June 2006) - Sanders, Julia; Campbell, Rona; Peters, Tim J
Abstract: Objectives To evaluate the effectiveness and acceptability of a lidocaine spray in reducing perineal pain during spontaneous vaginal delivery. Design Randomised controlled trial. Setting Consultant led obstetric unit. Participants 185 women who had a spontaneous vaginal delivery without epidural analgesia. Interventions Topically applied local anaesthetic spray (93 women) and placebo spray (92 women). Main outcome measure Primary outcome measure was pain during delivery (0-100 scale). The 16 secondary outcome measures included second degree perineal trauma during delivery, trauma of the genital tract, and dyspareunia by two months. Results Lidocaine spray did not reduce pain during spontaneous vaginal delivery: mean 77 and 72 on a scale of 0-100 in the lidocaine and placebo groups, respectively (difference between means 4.8, 95% confidence interval −1.7 to 11.2). Lidocaine spray may reduce genital tract trauma during delivery, in particular second degree perineal trauma. The intervention was highly acceptable to the women and midwives. Conclusions Although lidocaine spray applied to the perineum during spontaneous vaginal delivery did not reduce perineal pain, it was acceptable to both the women and the midwives. Trial registration Current controlled trials ISRCTN99732966 [controlled-trials.com] .